Construction of a simulation model of the work of a warehouse enterprise as a link in the logistics chain - Lebid, Ievgenii; Luzhanska, Nataliia; Lebid, Iryna; Mazurenko, Alexander; Mykhailenko, Iryna; Sharai, Svitlana (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the process of organizing the work of a warehouse enterprise when servicing customers. The task set is to devise recommendations for planning the staffing of a warehouse enterprise, taking into account the duration of rendering services to customers. A simulation model of the work of a warehouse enterprise when servicing customers has been built and implemented in the GPSS World simulation modeling automation package. The model involves determining the duration of warehouse service and determining the required number of personnel to enable the work of the business entity by areas of activity. When constructing the model, the duration of the types of work performed at individual stages of service performed by the warehouse enterprise personnel when processing foreign trade cargo was taken into account. In addition, the model takes into account the probability of errors and delays in rendering warehouse services at each stage of the business entity’s work, as well as the average delay time in the presence of errors. This can make it possible to determine the duration of additional employment of the enterprise personnel associated with the elimination of errors made in all types of work. Applying the devised model in practice will allow owners of warehouse enterprises to organize and plan activities of the business entity when servicing customers. This will also make it possible to determine the duration of rendering warehouse services when performing foreign trade operations, taking into account the indicators of the efficiency of specialists. At the same time, the probability of refusal to provide warehouse services to customers could decrease by 17% while the throughput capacity of the enterprise would increase by 22%